Advances in librarianship. Volume 33 - Woodsworth, Anne (Emerald, 2011)
This volume of Advances in Librarianship makes contributions to three largely unexplored areas in the field: managing intellectual capital in libraries, reporting on the effects of spatial factors and cooperation and competition upon intellectual capital utilization in libraries; Native American Libraries, offering findings which can apply in any country with ethnically or culturally isolated libraries; and the nature and extent of the engagement of humanities scholars with electronic texts. Other topics explored in this volume include the growth and decline of Operations Research both in general and within academic libraries, approaches to intellectual capital in libraries, and an historical analysis of the two streams of library education in Australia over 40 years. The Advances in Librarianship book series presents current international research and professional issues in libraries, the information industry, education and development of information professionals. The series is a key resource for practitioners, researchers, students and faculty members seeking in-depth literature and solutions to current and emerging issues in library and information science and related fields.
Includes indexes.
Keywords: Language Arts & Disciplines -- Library & Information Science -- General.; Business & Economics -- Budgeting.; Business & Economics -- Information Management.; Library, archive & information management.; Acquisitions & collection development.; Library science.; elektronické knihy; electronic books